HISTORY OF DEVELOPMENT OF THE LEGAL FRAMEWORK OF UZBEKISTAN IN THE FIELD OF ENVIRONMENTAL POLICY - Саидова Ш.Ш. (TARIXIY TADQIQOTLAR, 2025)
In this article, the author aims to identify the main areas of concentration of the legislation of the Republic of Uzbekistan in the period from 1991 to 2023 in relation to ecology and environmental policy of the country’s leadership, as well as to highlight the historical factors that contributed to changes in trends in the directions of the regulatory and legal ecopolitical framework. In this regard, the focus of the study is on a number of documents significant in this direction, omitting the enumerative nature of the transmission of information and data.